An international anomaly? Sovereignty, the League of Nations, and India's princely geographies - Legg, Stephen (Elsevier, 2014)
This paper examines India's experiences as the only non-self-governing member of the League of Nations as a means of addressing the broader question: where was the international? As the only non-self-governing member of the League, India's new international status exposed both its external, more imperial, as well as its internal, more colonial, anomalies. This paper examines, first, the Indian anomaly from the ‘inside out’, looking at India's representation and silencing at Geneva, and how Indian commentators assessed India's external status in the League. Secondly, it considers the Indian anomaly from the ‘outside in’, by exploring colonial tensions that the internationalism of the League provoked relating to India's internal political geography. The League posed taxing questions about the Government of India's decision to exclude international law from the spaces between British and Princely India, examined here through the example of trafficking in women and children. In exploring India's anomalous situation two broader approaches are deployed. The first is a scalar methodology, which shows how the concepts of the national and international operated at various scales, with India's burgeoning sense of nationhood taking one of its many shapes in the international sphere, while the internationalism of the League seeped into the national fissures between British and Princely India. Secondly, the paper approaches these questions through the lens of sovereignty. Moving beyond associations with the juridical and the territorial, it explores sovereignty as: representational (diplomacy); governmental (administration), theoretical (political philosophy), political (anti-colonialism), territorial (political geography) and contractual (international law).